Prospects for Treatment of Lung Cancer Using Activated Lymphocytes Combined with Other Anti-Cancer Modalities - Anastasia Ganina; Manarbek Askarov; Larissa Kozina; Madina Karimova; Yerzhan Shayakhmetov; Perizat Mukhamedzhanova; Aigul Brimova; Daulet Berikbol; Elmira Chuvakova; Lina Zaripova; Abay Baigenzhin (Advances in Respiratory Medicine)
This review explores the significance and prospects of using diverse T-cell variants in the context of combined therapy for lung cancer treatment. Recently, there has been an increase in research focused on understanding the critical role of tumor-specific T lymphocytes and the potential benefits of autologous T-cell-based treatments for individuals with lung cancer. One promising approach involves intravenous administration of ex vivo-activated autologous lymphocytes to improve the immune status of patients with cancer. Investigations are also exploring the factors that influence the success of T-cell therapy and the methods used to stimulate them. Achieving a comprehensive understanding of the characteristics of activated lymphocytes and deciphering the mechanisms underlying their activation of innate anti-tumor immunity will pave the way for numerous clinical trials and the development of innovative strategies for cancer therapy like combined immunotherapy and radiation therapy.